Congruence game: a dialogue between learning geometry and computational thinking - Viana, Lucas Henrique (2022)
Computational Thinking has been attracting attention from many teachers and researchers, however, there is a lack of studies that articulate it with the variety of content taught in schools. Considering this scenario, this article aims to investigate the ‘Congruences game’ as a dialogue between geometry learning and computational thinking. This research focuses on a qualitative approach and has been applied to eight students from 8th grade of a public school at Campina Grande, Paraíba (Brazil). The results revealed students’ ability to develop different strategies to verify the congruence and non-congruence of triangles, wich can be associated with computational thinking abilities. They also pointed to the possibility of new studies about computational thinking and its associations with other scholar content.